Indonesian Education Autonomy: A Bibliographic Study - Rizki Erdayani; Muslim Afandi; Syed Agung Afandi (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to analyse the trend of educational autonomy in Indonesia. This study used a qualitative approach with a bibliometric analysis method. This study uses data from 2012–2022, sourced from the Google Scholar database and obtained using the Publish or Perish application. The data is then processed using the Vosviewer application to obtain a bibliometric map. The results of this study indicate that the study of Indonesian educational autonomy is quite attractive to researchers. Even though it fluctuated, in the span of the last decade, there were 205 papers on Indonesian education autonomy that had been cited 3075 times. From these figures, an h-index score of 11 and a g-index score of 55 are obtained. There are a total of 309 keywords, 1380 total link strengths, and 863 occurrences. These keywords are grouped into 79 clusters, with a varying number of keywords in each cluster. The keywords that dominate the study of Indonesian educational autonomy are: school based management, teacher, educational facility, education costs, and curriculum. In other words, the study of Indonesian educational autonomy focuses on these issues